Use of Recyclable Materials in the Interior Design - Lubonja, Otjela; Dervishi, Albina (European Journal of Economics and Business Studies, 2019)
This paper is the subject of the Bachelor’s Degree by Albina Dervishi under the guidance of the lecturer Dr. Otjela Lubonja. Through this study, it is intended to show what is recycling, what is its impact on nature and society. As an efficient process for the handling and reuse of materials, which promotes innovation and an important and long-term economic growth. Equally important are both social and environmental benefits because it promotes the sustainable use of our natural resources and fosters community development, saving of new land use, pollution prevention, energy conservation and reduction of greenhouse gas effects. To tell us at what stage of our recycling is our country and whether we have it or not as a culture. To explain what it means to use indoor and outdoor recyclable materials and what these materials are. The paper continues to detail how recyclable materials are selected in detail from their chemical and structural composition as these materials can be applied to the interior and exterior. In practice, it is unlikely to achieve this ideal in the near future most of the construction companies in Albania. However, a significant contribution that the society itself, but also the construction industry can do, is to link design and ecology to building buildings and buildings without harming the environment. So use the design in such a way as to make possible the reuse and recycling of the materials used. The work at the current stage was supported by secondary data, the study at a second stage could be extended to public policy presented as a project for its realization, in public institutions such as municipal units, city hall. Through this paper, UET draws the attention of the country’s scientific opinion and beyond to the opportunities created for in-depth studies in the field of Architecture and Design Sciences.